Object-oriented modeling of patients in a medical federation. - Proctor, M.D.
Explores the development of an object-oriented model to support the inter-operation of simulations within a federation for the purpose of conducting medical analysis and training over a distributed infrastructure. The medical federation is referred to as the Combat Trauma Patient Simulation System and is composed using a high-level architecture. The infrastructure contains components that were separately developed and are heterogeneous in nature. This includes a general anatomical database that is capable of analyzing human injuries, referred to as operational requirements-based casualty assessment, an animated mannequin called the Human Patient Simulator, and other components. The research develops an object model that enables bodily injury data to be shared across the simulation, conducts analysis on that data and considers possible applications of the technique in expanded medical infrastructures.
Keywords: Combat Trauma Patient Simulation System; Human Patient Simulator; Anatomical database; Animated mannequin; Biomedical education; Bodily injury data; Data analysis; Data sharing; Distributed infrastructure; Expanded medical infrastructures; Heterogeneous components; High-level architecture; Human injuries; Medical analysis; Medical federation; Medical training; Object-oriented model; Operational requirements-based casualty assessment; Patient modeling; Simulation interoperation